Effect of growth substances on growth, flowering and corm production in gladiolus (Gladiolus grandiflorus) cv White Prosperity under Bay Island conditions - BASKARAN, V; ABIRAMI, K (The Indian Journal of Agricultural Sciences, 2016)
Field experiment was conducted for two consecutive seasons during November-April of the years 2011-12 and 2012-13 in the Division of Horticulture and Forestry, Central Island Agricultural Research Institute, Port Blair to study the effect of plant growth regulators on gladiolus (Gladiolus grandiflorus Hort.) cv. White Prosperity. The results revealed that various growth, flowering and corm characters were significantly affected with the application of different growth regulators at different concentrations. Earliness in corm sprouting was observed by GA3 at 500 ppm (10.6 days) .Maximum number of leaves/plant and plant height was obtained by GA3 at 750 ppm (8.2 and 111.0 cm respectively). More number of shoots per corm was observed by BA at 100 ppm (3.7). In respect of flower characters early spike emergence and maximum duration of the spike was recorded by GA3 at 500 ppm (49.0 days and 17.5 days respectively). Maximum spike length, rachis length and number of florets per spike (79.3 cm, 56.5 cm and 14.7 respectively) were recorded by GA3 at 750 ppm. In respect of corm characters maximum number of corms and cormels per plant was observed in BA 100 ppm (3.4 and 19.3 respectively). Maximum weight of single corm, weight of corms/plant, size of single corm and volume of single corm (77.5 g, 189.1 g, 7.6 cm and 86.3cc respectively) were recorded in GA3 at 750 ppm. Maximum weight of cormels per plant was recorded in BA at 100 ppm (7.1g). Maximum value of propagation co efficient was recorded in GA3 at 750 ppm (386.4%).